Diversity and composition of herbaceous angiosperms along gradients of elevation and forest-use intensity. - Jorge Antonio Gómez-Díaz; Thorsten Krömer; Holger Kreft; Gerhard Gerold; César Isidro Carvajal-Hernández; Felix Heitkamp (PLoS ONE)
Terrestrial herbs are important elements of tropical forests; however, there is a lack of research on their diversity patterns and how they respond to different intensities of forest-use. The aim of this study was to analyze the diversity of herbaceous angiosperms along gradients of elevation (50 m to 3500 m) and forest-use intensity on the eastern slopes of the Cofre de Perote, Veracruz, Mexico. We recorded the occurrence of all herbaceous angiosperm species within 120 plots of 20 m x 20 m each. The plots were located at eight study locations separated by ~500 m in elevation and within three different habitats that differ in forest-use intensity: old-growth, degraded, and secondary forest. We analyzed species richness and floristic composition of herb communities among different elevations and habitats. Of the 264 plant species recorded, 31 are endemic to Mexico. Both α- and γ-diversity display a hump-shaped relation to elevation peaking at 2500 m and 3000 m, respectively. The relative contribution of between-habitat β-diversity to γ-diversity also showed a unimodal hump whereas within-habitat β-diversity declined with elevation. Forest-use intensity did not affect α-diversity, but β-diversity was high between old-growth and secondary forests. Overall, γ-diversity peaked at 2500 m (72 species), driven mainly by high within- and among-habitat β-diversity. We infer that this belt is highly sensitive to anthropogenic disturbance and forest-use intensification. At 3100 m, high γ-diversity (50 species) was driven by high α- and within-habitat β-diversity. There, losing a specific forest area might be compensated if similar assemblages occur in nearby areas. The high β-diversity and endemism suggest that mixes of different habitats are needed to sustain high γ-richness of terrestrial herbs along this elevational gradient.